2010
DOI: 10.1007/s10482-010-9456-y
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic affiliation of the desert truffles Picoa juniperi and Picoa lefebvrei

Abstract: The molecular phylogeny and comparative morphological studies reported here provide evidence for the recognition of the genus Picoa, an hypogeous desert truffle, in the family Pyronemataceae (Ascomycota, Pezizales). Picoa juniperi and Picoa lefebvrei were reassigned to the genus Picoa based on large subunit (LSU) sequence (28S) rDNA and internal transcribed spacer (ITS) rDNA (including the partial 18S, ITS1, ITS2, 5.8S gene, and partial 28S of the nuclear rDNA) data. Morphological studies of spores, asci, peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…The results of this study revealed Geopora (except G. pellita) as a monophyletic group using maximum-parsimony and Bayesian analyses, but neither Phaeangium nor Picoa were included in the dataset. Using either 28S or ITS rDNA sequence data, our analyses place these two genera within a paraphyletic Geopora with high confidence, at least under the maximum-likelihood criterion, in agreement with the results obtained by Guevara-Guerrero et al (2011) and Sbissi et al (2010), and highlighting the importance of sufficient taxon sampling. Because Sepultaria already exists as a validly published name for the apothecial Geopora spp., there is little reason for not using it once again for these fungi.…”
Section: Classification Of G Pellita Relative To Geopora and Tricharinasupporting
confidence: 89%
“…The results of this study revealed Geopora (except G. pellita) as a monophyletic group using maximum-parsimony and Bayesian analyses, but neither Phaeangium nor Picoa were included in the dataset. Using either 28S or ITS rDNA sequence data, our analyses place these two genera within a paraphyletic Geopora with high confidence, at least under the maximum-likelihood criterion, in agreement with the results obtained by Guevara-Guerrero et al (2011) and Sbissi et al (2010), and highlighting the importance of sufficient taxon sampling. Because Sepultaria already exists as a validly published name for the apothecial Geopora spp., there is little reason for not using it once again for these fungi.…”
Section: Classification Of G Pellita Relative To Geopora and Tricharinasupporting
confidence: 89%
“…With regard to bacteria that have been well explored in southern desert region of Tunisia [2831], data related to fungi are scarce and are limited to truffle and mycorrhiza, so far considered as real specialists of desert environments [32, 33]. To the best of our knowledge, this is the first report on the isolation and characterization of fungi from Tunisian desert and particularly from salt flat.…”
Section: Discussionmentioning
confidence: 99%
“…uncinatum, with a blackish brown peridium with polygonal warts. The gleba is white with fertile tissue separated by sterile veins [34] and a sweet smell and coconutlike flavor that is altered when parasitized by Melanospora zobelii. With six-eight oval ascospores per asci, P. juniperi is differentiated from P. lefebvrei by its smooth appearance [34].…”
Section: Picoa Juniperi Vittadmentioning
confidence: 99%
“…The gleba is white with fertile tissue separated by sterile veins [34] and a sweet smell and coconutlike flavor that is altered when parasitized by Melanospora zobelii. With six-eight oval ascospores per asci, P. juniperi is differentiated from P. lefebvrei by its smooth appearance [34]. The small size of ascocarps, i.e., 1-3 cm, limits the market potential of this species but it is readily consumed when found with other desert truffle species.…”
Section: Picoa Juniperi Vittadmentioning
confidence: 99%
See 1 more Smart Citation